HUMAN SPIRITUALITY PHASES IN SUFISM The Study of Abu Nasr Al-Sarraj in The Book of al-Luma' - Mukholik, Ayis (Teosofia: Indonesian Journal of Islamic Mysticism, 2017)
This study discusses the phases that human beings must go through to achieve a noble degree in the sight of God. In Sufism, this topic is known as maqamat and ahwal. Maqamat is the spiritual position, that is, the existence of a person in the way of Allah by trying to practice the deeds to be closer to Allah. While ahwal is a condition or spiritual circumstance within heart bestowed by God because of the intensity of the dhikr (remembering God). To reach the highest level (ma'rifatullah), it can not be reached in a way that is easy and short time. Man must try to empty himself from sin and fill it with good deeds. For only with a holy soul, God gives much of His knowledge. This paper aims to describe and analyze the stages of human spirituality in the book of a classic Sufi figure, Abu Nasr Al-Sarraj. Through inner experience, Sarraj formulated the concept of being close to God. This thought is based on the social conditions of society at that time concerning with material matters rather than spiritual ones. Therefore, the question is how the spiritual phases should be achieved by Al-Sarraj? To answer this question, the researcher uses a qualitative method by examining the text and analyzing it to find the sequences of phases. The result of this research is that Al Sarraj formulates 7 levels of maqam and 9 levels ahwal. Humans who can run the phase are classified into Insan Kamil (perfect human) because there is no distance between him and God.